Comparative analysis of conventional penile clamps and Uriclak device in managing male incontinence following radical, turp, or laser prostate surgery - Ten, Eva (Frontiers in Surgery, 2023)
This article examines the impact of various prostate surgery techniques on male urinary incontinence, evaluating the feasibility, efficacy, and safety of penile clamps as a post-prostate surgery treatment. The study compares the characteristics and applications of conventional penile clamps and the Uriclak urethral compression device, highlighting their differences and potential for managing male incontinence.